Astrocytic glutamine synthetase is expressed in the neuronal somatic layers and down‐regulated proportionally to neuronal loss in the human epileptic hippocampus. Issue 5 (19th January 2018) - Papageorgiou, Ismini E.; Valous, Nektarios A.; Lahrmann, Bernd; Janova, Hana; Klaft, Zin‐Juan; Koch, Arend; Schneider, Ulf C.; Vajkoczy, Peter; Heppner, Frank L.; Grabe, Niels; Halama, Niels; Heinemann, Uwe; et al.
Abstract: Human mesial temporal lobe epilepsy (MTLE) features subregion‐specific hippocampal neurodegeneration and reactive astrogliosis, including up‐regulation of the glial fibrillary acidic protein (GFAP) and down‐regulation of glutamine synthetase (GS). However, the regional astrocytic expression pattern of GFAP and GS upon MTLE‐associated neurodegeneration still remains elusive. We assessed GFAP and GS expression in strict correlation with the local neuronal number in cortical and hippocampal surgical specimens from 16 MTLE patients using immunohistochemistry, stereology and high‐resolution image analysis for digital pathology and whole‐slide imaging. In the cortex, GS‐positive (GS+) astrocytes are dominant in all neuronal layers, with a neuron to GS+ cell ratio of 2:1. GFAP‐positive (GFAP+) cells are widely spaced, with a GS+ to GFAP+ cell ratio of 3:1–5:1. White matter astrocytes, on the contrary, express mainly GFAP and, to a lesser extent, GS. In the hippocampus, the neuron to GS+ cell ratio is approximately 1:1. Hippocampal degeneration is associated with a reduction of GS+ astrocytes, which is proportional to the degree of neuronal loss and primarily present in the hilus. Up‐regulation of GFAP as a classical hallmark of reactive astrogliosis does not follow the GS‐pattern and is prominent in the CA1. Reactive alterations were proportional to the neuronal loss in the neuronal somatic layers (stratum pyramidale and hilus), while observed to a lesser extent in the axonal/dendritic layers (stratum radiatum, molecular layer). We conclude that astrocytic GS is expressed in the neuronal somatic layers and, upon neurodegeneration, is down‐regulated proportionally to the degree of neuronal loss. Main Points: Glutamine synthetase in human cortex and hippocampus is expressed by astrocytes in the neuronal somatic layer. Downregulation of glutamine synthetase in hippocampal sclerosis is proportional to the neuronal loss.